Earlobe Keloid Management- A RCT of Intra-Lesional Excision With Intra- & Post-Operative Steroids Versus Intra-Lesional Excision With Post-Operative Steroids (Bangladesh Journal of Plastic Surgery, 2010)
A prospective, randomized controlled trial was designed to compare the outcome of earlobe keloid management by intra-lesional excision with intraoperative and two dose post-operative steroid injections versus intra-lesional excision with two doses post-operative steroid injections. Total 87 patients having 100 earlobe keloids were enrolled in the study with 50 keloids in each group allocated by lottery, but only 69 completed two years follow up. The age of the patients ranged from 15 to 40 years and all were female. Trauma from piercing ear lobule for earring was the main cause of keloid initiation. Both the groups were homogeneous preoperatively regarding age of patients, pre-operative volume of keloids, pattern of previous treatment received, patient's skin complexion and patient’s family history of keloid.Intra-lesional excision keeping 1mm margin followed by intra-operative steroid injection was given in one group and without steroid injection in other group. Residual keloid volume (length, Breath, and height) was measured intra-operatively and post-operatively during follow up period by blindfolded observers. Any symptomatic relief as well as local and systemic side effects of steroids were also recorded.Main observation of this study after two years was 8.3% recurrence in intra-lesional excision with intra-and two dose post-operative steroid injections and 21.2% recurrence in intra-lesional excision with two dose postoperative steroid injections. This difference was not statistically significant (p = 0.177). But, the former protocol reduced recurrence significantly during 1st one year follow up. Residual keloid volume reduction was faster in former protocol in early post-operative period, but not in later period. Symptomatic improvement was also faster in the former protocol, in early post-operative period, but no difference in later period. Local side effects and systemic side effects of steroid were more or less equal in both protocols.The study demonstrates that additional intra-operative steroid injection has better effect in early post-operative period in managing earlobe keloid, but has no significant effect in long term follow up.DOI: http://dx.doi.org/10.3329/bdjps.v1i1.6489Bangladesh Journal of Plastic Surgery (2010) Vol. 1 (1) pp.24-28